Inteligencia emocional y su influencia en la convivencia escolar de niños de educación inicial 2 - Vega Navarrete, Daniela Mariela (2024)
The present work has the purpose of detailing in a global way the influence that emotional intelligence has on the behavior of school coexistence in the children of Initial II in which it is proposed to look for solutions through the study of these variables, the objective is to establish the influence of emotional intelligence on school coexistence in the children of Initial Education II of the Santo Domingo Educational Unit. By means of descriptive research with a mixed approach, a non-experimental design applying inductive and deductive methods with a documentary and field research. As a non probabilistic sample, 30 children, 2 teachers, 30 parents will be taken, where we will use the survey and observation technique and as an instrument we will use the questionnaire and the observation form. In conclusion, it is vital to help improve emotional intelligence because through this it will be possible to stimulate children to a dynamic society, with an acceptable coexistence which was evidenced by the result of applying tactics was found in average level of children who show impulsive attitudes that reflect the deficiency of their emotions, some who do not have a good coexistence with their peers, are easily distracted in class, and others have behavioral problems.